Global Financial Crises in Post-Socialist Countries:Consumption, Economic Life and Consumer Cultures - Marina Spirina (Journal of Economic Sociology, 2014)
The research workshop “Consumption and Economic Crises: Post-Socialist Experiences” was held on October 9−10, 2014 at the National Research University Higher School of Economics in Moscow. Organized by Sandy Ross (Senior Lecturer, Leeds Beckett University) and Christopher S. Swader (Assistant Professor, Department of Sociology, HSE), the workshop explored experiences of global financial crisis in post-socialist countries with an emphasis on the everyday urban consumption culture in the first decade of the 21st century. The workshop focused on four aspects of post-socialist consumer culture: housing and credit practices; gift-giving, hospitality and reciprocity practices; consumption practices and consumption ethics; and aesthetics. One of the goals of this conference was also to explore the disjunctions and continuities between consumer cultures and experiences of “crisis” within and between post-socialist countries and other countries.Each day of the conference began with a keynote presentation followed by two moderated panel sessions in which relevant and on-going research was presented by invited speakers. At the conclusion of each panel session, the floor was opened for discussion and debate among all workshop participants.The keynote speakers of the workshop were Alya Guseva (Boston University, USA) and Olga Shevchenko (Williams College, USA). The invited speakers were Marta Olcoń-Kubicka (Polish Academy of Science, Warsaw), Ferenc Hammer (ELTE-BTK, Institute for Art Theory and Media Studies, Hungary), Mateusz Halawa (The New School for Social Research, Poland), Elizaveta Polukhina and Anna Strelnikova (HSE, Russia), Costanza Curro’ (University College London, UK), Natalia Khalina and Alina Pishniak (HSE, Russia), Natalia Firsova (HSE, Russia), Vadim Radaev (HSE, Russia), Zoya Kotelnikova (HSE, Russia), Eileen Yuk-ha Tsang (City University of Hong Kong) and Radostina Schivatcheva (King’s College London, UK). Sandy Ross acted as lead moderator. The conference attracted a wide audience, including students and researchers from various different countries.